2009
DOI: 10.1002/jcb.22110
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively activated RAW264.7 macrophages enhance tumor lymphangiogenesis in mouse lung adenocarcinoma

Abstract: Tumor-associated macrophages (TAMs) have been implicated in promoting tumor progression and invasion. The onset and maintenance of tumor angiogenesis and lymphangiogenesis also seem to be partly driven by a group of polarized alternatively activated macrophages (aaMphi) in lung adenocarcinoma. Here, the aaMphi and classically activated macrophages (caMphi) were obtained using RAW264.7 cells via IL-4 and IFN-gamma + LPS treatment, respectively. Co-inoculation of aaMphi with Lewis lung carcinoma (LLC) cells prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
(54 reference statements)
4
34
0
Order By: Relevance
“…Recently, Mantovani et al found that TAMs might be polarized toward an aaMphi phenotype [22]. In our previous study, we reported that alternatively activated TAMs can induce peritumoral lymphangiogenesis in mouse Lewis lung adenocarcinoma [16]. Briefly, coinoculation of aaMphi with Lewis lung carcinoma (LLC) cells promoted tumor growth, increased lymph node metastasis and reduced the survival in C57BL/6 mice bearing LLC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, Mantovani et al found that TAMs might be polarized toward an aaMphi phenotype [22]. In our previous study, we reported that alternatively activated TAMs can induce peritumoral lymphangiogenesis in mouse Lewis lung adenocarcinoma [16]. Briefly, coinoculation of aaMphi with Lewis lung carcinoma (LLC) cells promoted tumor growth, increased lymph node metastasis and reduced the survival in C57BL/6 mice bearing LLC.…”
Section: Discussionmentioning
confidence: 96%
“…Schoppmann et al reported that the peritumoral inflammatory reaction and vascular endothelial growth factor (VEGF)-C expressing TAMs increase tumor lymphangiogenesis and lymphovascular invasion in cervical cancer [14] and invasive breast cancer [15]. Recently, we reported that similar to TAMs, alternatively activated macrophages have a potent effect on the lymphangiogenesis-related properties of lymphatic endothelial cells (LECs) though up-regulating VEGF-C expression and secretion [16]. However, in lung adenocarcinoma, the correlation between TAMs infiltration and peritumoral lymphangiogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Formation of tube-like structures was monitored by microscopic observation at a magnification of x100 over 6 different fields of each well. They were then photographed to measure the length of tube-like structures as previously described (19).…”
Section: Methodsmentioning
confidence: 99%
“…As the major inflammatory component of the stroma of many tumors, tumor-associated macrophages (TAMs) can affect different aspects of the neoplastic tissue [1,5]. Recent experimental studies indicate that TAMs play a detrimental protumor role in the initiation of tumorigenesis, promotion of angiogenesis and lymphangiogenesis, growth, invasion and metastasis of tumor cells and the suppression of adaptive immunity [1,[5][6][7][8]. Clinical studies have shown that a high density of these TAMs correlates with a poor prognosis in over 80% of studies published, such as those in breast, prostate, cervical and ovarian cancers [9].…”
Section: Introductionmentioning
confidence: 99%